SPATIAL MODELING OF ENVIRONMENTAL-BASED RISK FACTORS OF TUBERCULOSIS IN BALI PROVINCE: AN ECOLOGICAL STUDY - Firman Firdauz Saputra; Chatarina Umbul Wahjuni; Muhammad Atoillah Isfandiari (Jurnal Berkala Epidemiologi, 2020)
Background: Indonesia is one of countries with a quite high incidence of tuberculosis. One of the regions which has issue of tuberculosis incidence is Bali Province with a case notification rate that tends to increase in the last three years so that it has an impact on increasing the risk of disease transmission. Purpose: This research aims to identify the risk factor based on the environment/spatial incidence of the tuberculosis in Bali Province. Methods: This research used ecological study design through secondary data obtained from the Health Office of Bali Province, Indonesian Statistics of Bali Province, and Environmental Office of Bali Province. The dependent variable was tuberculosis incidence, while the independent variable was the level of PM10, population density, poverty percentage, healthy house percentage, percentage of Clean and Healthy Lifestyle (PHBS), ratio of healthcare facilities with the community. Results: The statistical model was obtained in the form of Spatial Error Model (SEM) with model ŷi=1612,57+ 0,96 * level of PM10 + 0,04 * population density - 2,56 * poverty - 0,58 * Healthy house - 3,099 * PHBS - 0,006 * health care facility, where μi  = 0,90  . Conclusion: The risk factor spatially affected the tuberculosis incidence in Bali Province, which were the factors of level of PM10, population density, poverty percentage, healthy house percentage, percentage of PHBS, and ratio of healthcare facilities with the community.